1980
DOI: 10.1111/j.1600-0765.1980.tb00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Kielbone® in healing interradicular lesions in monkeys

Abstract: The purpose of this investigation was, to compare the histological features of Kielbone and autogenous jaw bone following transplantation into periodontal interradicular lesions in monkeys. Bifurcation defects were produced on mandibular molars and premolars. Kielbone was transplanted into 40 bifurcations while another 30 bifurcations received fresh autogenous cancellous jaw bone. The animals were sacrificed according to a schedule yielding observation periods up to 16 weeks. Before sacrifice the animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…It is well known that intimate interactions occur between collagens and biological apatites in vivo. 20,40 These observations, in conjunction with our previous studies, 24 indicate that this three-dimensional culture system may provide osteoblast-like cells with an environment more similar to in vivo conditions than the collagen lattice gel 23 or the monolayer culture.…”
Section: Discussionsupporting
confidence: 76%
“…It is well known that intimate interactions occur between collagens and biological apatites in vivo. 20,40 These observations, in conjunction with our previous studies, 24 indicate that this three-dimensional culture system may provide osteoblast-like cells with an environment more similar to in vivo conditions than the collagen lattice gel 23 or the monolayer culture.…”
Section: Discussionsupporting
confidence: 76%
“…Clinical (Scopp et al 1966, Older 1967) and histological (Arrocha et al 1968, Nielsen et al 1980, 1981 studies promoted the use of anorganic bovine bone for grafting in intra-osseous defects. In this context, an anorganic xenograft (Bio-Oss s , Geistlich Pharma AG, Wolhusen, Switzerland) was developed for bone regeneration procedures.…”
mentioning
confidence: 99%
“…The periodontal ligament suspends the tooth like a cushion in order transduce the mechanical load from the teeth evenly onto the supporting bone. Early studies of different animal models demonstrated that the periodontal tissues possess some regeneration activity, suggesting the existence of stem cell population within the periodontium (Karring et al, 1980; Nielsen et al, 1980; Nyman et al, 1980, 1982; Parlar et al, 2005). After depletion of various periodontal tissues, not only the periodontal ligaments, but also cementum and alveolar bone, can be regenerated, suggesting the presence of multipotential stem cell populations (Nielsen et al, 1980; Nyman et al, 1982; Parlar et al, 2005).…”
Section: Periodontium Tissue Regeneration and Stem Cellsmentioning
confidence: 99%
“…Early studies of different animal models demonstrated that the periodontal tissues possess some regeneration activity, suggesting the existence of stem cell population within the periodontium (Karring et al, 1980; Nielsen et al, 1980; Nyman et al, 1980, 1982; Parlar et al, 2005). After depletion of various periodontal tissues, not only the periodontal ligaments, but also cementum and alveolar bone, can be regenerated, suggesting the presence of multipotential stem cell populations (Nielsen et al, 1980; Nyman et al, 1982; Parlar et al, 2005). Studies conducted on the human periodontium indicate the presence of a putative PDLSCs population (Seo et al, 2004), positive for MSC markers including STRO-1 and CD146 and able to differentiate into osteoblasts, adipocytes, and cementoblasts (Seo et al, 2004).…”
Section: Periodontium Tissue Regeneration and Stem Cellsmentioning
confidence: 99%